DETERMINATION OF FRUIT DEVELOPMENT STAGES AND PRODUCTION OF DATES IN KHAIRPUR SINDH PAKISTAN - Jamro, Muhammad Mahmood-Ur-Rahman; Abbasi, Zulfiqar Ali; Chandio, Ali Sher (Bangladesh Journal of Multidisciplinary Scientific Research, 2021)
The study was conducted to record fruit development stages of nine Date palm cultivars from spathe initiation to harvest. The data was recorded as per each parameter; finally mean days were calculated at completion of each fruit development stage. The results revealed that all cultivars initiated spathes from 8th January to 26th February. Significant differences were recorded in all physiological fruit development stages. The minimum period of (13.66 days) and maximum (24.00 days) were taken by Shakri and Begum jangi respectively up to the spathe maturity stage, whereas Aseel taken (14.33 days) and Dhaki recorded (27.00 days) to pollination. In the fruit setting (Hababuk stage) Hussaini noted minimum period of (44.33 days) and Muzawati observed maximum (57.66 days). In Doka formation (Kimri stage, the Hussaini cultivar recorded lowest period of (71.33 days) and Muzawati taken highest (99.33 days). Up to mature fruit (khalal stage) Begum jangi attained the minimum (110.33 days). However Fasli and Dhakki observed the maximum (153.67 days). At Rutab stage, the cultivar Begum jangi recorded lowest harvesting period (118.33 days) and Dhaki noted highest (158.00 days). In relation to the maximum yield Dhaki recoded (169.00 kg/plant) and Hussaini produced minimum yield (97.00 kg/plant).